1980
DOI: 10.1159/000153161
|View full text |Cite
|
Sign up to set email alerts
|

Heritable Salivary Proteins and Dental Disease

Abstract: A sample consisting of 92 black subjects was examined in this study. According to results of preliminary statistical tests there is a significant relationship between certain genetically determined salivary factors and individual susceptibility to dental disease in the racial group studied. These findings are being validated by the examination of data from several additional studies involving large samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

1986
1986
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 4 publications
(4 reference statements)
0
7
1
Order By: Relevance
“…Antibody detection is impractical, because the additional amino acid sequence that characterizes Db duplicates part of the Pa and Pif sequences (Azen et al, 1987). The findings of this study call into question the reported association of Db gene expression with greater caries experience in African-American adults (Friedman et al, 1980). Compared with African-Americans, the caries experience of Db-positive Caucasians was less in magnitude and not significant.…”
Section: Discussioncontrasting
confidence: 64%
“…Antibody detection is impractical, because the additional amino acid sequence that characterizes Db duplicates part of the Pa and Pif sequences (Azen et al, 1987). The findings of this study call into question the reported association of Db gene expression with greater caries experience in African-American adults (Friedman et al, 1980). Compared with African-Americans, the caries experience of Db-positive Caucasians was less in magnitude and not significant.…”
Section: Discussioncontrasting
confidence: 64%
“…In Db, a 63-bp sequence in exon 3 is repeated (1), making the protein about 12% longer. A. naeslundii attachment to apatite coated with Db-positive saliva is inhibited, whereas that of S. mutans is enhanced and the subjects have a significantly greater caries experience (14,42).…”
Section: Discussionmentioning
confidence: 96%
“…In this location the PRP may also act as receptors for commensal and pathogenic organisms which colonize teeth, and recently the PRP have been identified as selective mediators of bacterial adhesion to hydroxyapatite (Gibbons & Hay, 1988a,b), which is the prototype mineral for dental enamel. This observation seems highly significant in that differences in the phenotypic expression of the PRPs have been related to variations in oral disease (Friedman et al, 1980;Yu et al, 1986). All the foregoing properties depend on structural features of the PRPs (Bennick et al, , 1981Moreno et al, 1982Moreno et al, , 1984Aoba et al, 1984;Hay et al, 1987).…”
Section: Discussionmentioning
confidence: 99%